The Complexities of Implementing Gazetted Fatwas in Malaysia's Federal Territories - Zainal Abidin, Nur Hazirah; Nasohah, Zaini (Mazahib, 2023)
In Malaysia, non-compliance with a fatwa constitutes a breach under Shariah criminal jurisprudence. In such violations, it is imperative to undertake appropriate enforcement measures to address and mitigate the issue effectively. However, the implementation of enforcement has many challenges. One of the main challenges in enforcing a Shariah criminal offense is to meet the elements of proof for each offense committed. This article aimed to discuss some of the challenges regarding the enforcement of fatwas in the Federal State Territory. This research adopts a qualitative methodology, employing document analysis as a primary tool for data collection. Additionally, the study utilizes interviews to gather insights about the challenges encountered in enforcing fatwas within the community. The collected data is subsequently subjected to descriptive analysis for a comprehensive understanding. The results of the study found that among the main challenges faced by the Enforcement Division of the Federal Territory Islamic Religious Department (JAWI) are the weakness in fulfilling the elements of proving the wrongdoing of the fatwa, lack of specific expertise in matters related to investigation and intelligence as well as a lack of enforcement officers. This situation significantly influences the enforcement department's capacity to implement fatwa compliance measures within this state effectively.